Dental root periapical resorption caused by orthodontic treatment - Pinandi Sri Pudyani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2006)
Dental root resorption especially in maxillary incisive region almost always happens simultaneously with orthodontic treatment, and it gained researchers attention, in particular after the use of periapical radiography. However, the fundamental etiology of dental root resorption is still dubious. Multifactoral causes are mentioned, among others are hormonal, nutritition, trauma, dental root form and dental root structure anomalies, genetic, while from treatment side are duration, types, strength scale and dental movement types. Based on these findings, orthodontic treatment was proven to cause dental root resorption in maxillary incisive teeth.